ANALISIS PERLAKUAN AKUNTANSI ATAS ZAKAT, INFAQ, DAN SHADAQAH BERDASARKAN PSAK 101 DAN 109 PADA LAZISMU BEKASI - Ratna Widyatami; Siti Nurlatifah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
The purpose of the research is to analyze the suitability of the application of zakat accounting based on SFAS 109 and SFAS 101 in the financial statements of LAZISMU Bekasi. Zakat and infaq/shadaqah funds managed by zakat management institutions need to be accounted for through financial reporting. Quality financial statements can reflect the quality of performance and accountability of the institutions.The results showed that the accounting treatment of zakat in LAZISMU Bekasi was still very simple, in the form of cash receipts and disbursements. LAZISMU Bekasi has not been able to make a complete and informative financial report. The incompatibility of the financial statements of LAZISMU Bekasi woth SFAS is due to lack of understanding and a lack of experts in financial position of the institutions.The financial statements of LAZISMU Bekasi are not yet in accordance with SFAS because they have not presented a Financial Position Report, a Fund Change Report, a Change in Asset Mangement Report, a Cash Flow Report, and Notes to Financial Statements. LAZISMU Bekasi should routinely take part in socialization and training to improve amil competency. So that it is expected that Amil LAZISMU Bekasi can implement financial statements in accordance with SFAS.